Recent progress in well-defined higher azaacenes (N ≥ 6) : synthesis, molecular packing, and applications - Zhang, Zhongbo (2021)
In this review, we will focus on the recent progress in the synthetic strategies, photo-electronic properties, molecular packing modes and applications of azaacenes (n ≥ 6) with single-crystal structures. We will summarize the synthetic methods to approach larger azaacenes and elaborate the relationships between their molecular structures (solid stacking) and their photo-electronic properties. Moreover, the device applications of azaacenes as organic semiconductors are also reviewed.